Inward foreign direct investment and transfer of environmentally sound technology in Angola - Manyuchi, Albert E. (South African Journal of Science, 2016)
Many developing countries have relied on foreign direct investment as a primary means to acquire technologies. However, there has been inadequate empirical research on the nexus between foreign direct investment and the transfer of environmentally sound technology (EST), specifically focused on African countries. In this paper I explore whether inward foreign direct investment in Angola’s energy sector has indeed transferred ESTs. My study encompasses illustrative case studies specifically related to energy firms, and the data were drawn from literature and in-depth individual interviews. The results indicate that Angola has used its national policy framework and institutions to promote inward foreign direct investment, and has harnessed appropriate international regimes to acquire ESTs. Countries may therefore invoke sovereignty principles enshrined in constitutional provisions, or may utilise international regimes to attract ESTs through foreign direct investment. I recommend that further studies be conducted to explore this subject area, drawing examples from other African countries and differing economic sectors.